EVALUATING THE FACTORS SHAPING THE IMPLEMENTATION OF PUBLIC ROAD MANAGEMENT POLICIES A STUDY IN BANGKA BELITUNG ISLANDS - Nugraha, Niko; Sujarwoto, S; Amirudin, Akhmad (Erudio Journal of Educational Innovation, 2025)
This study analyzes the implementation of public road management policy in the Bangka Belitung Islands using Edward III’s framework: communication, resources, bureaucratic structure, and disposition. It investigates how these factors differ across administrative levels national, provincial, city, and regency and how they influence policy outcomes. Additionally, the study identifies the most pivotal factor and introduces politics and innovation as additional influences. Using a qualitative descriptive method, the research draws on semi-structured interviews with Echelon 3 officials and secondary data from road management agencies. Data was analyzed through thematic analysis using NVivo. The findings reveal that resources, especially budget and human resources, are the most critical and frequently discussed factors. These elements also strongly influence other aspects of implementation. The study finds significant disparities in implementation capacity, with regency-level agencies facing the greatest challenges due to limited resources. Political dynamics and innovation practices also affect implementation either positively or negatively, depending on the context. These findings underscore the need for equitable resource distribution, standardized procedures, and improved institutional resilience to strengthen road policy implementation in decentralized governance systems.